Organizational Commitment, Transformational Leadership and Organizational Culture on Turnover Intention of Retail and Services Industry in Malaysia - Goh Lin Kin (Lincoln), Awanis Ku Ishak (International Journal of Advanced Science and Technology, 2020)
High Frontline-employees’ turnover has continuously been a subject of concern to both academicians and practitioners of both developed and developing worlds.  In Malaysia, the retail and services employees' turnover rate was at 18%.  Incidentally, one of the greatest challenges that retail and services industry face is a lack of employee commitment.  The objective of this study is to research on framework of how to assist retail and services industry in Malaysia to attain sustainable high performance by reducing high employees’ turnover through the utilization of the Theory of Reasoned Action (TRA) as the underpinning theory to study on how intention is dependent on reason where it mediates the relationship between attitude and behaviour, of which the management’s beliefs (in this study are the transformational leadership and organizational culture) influence organizational commitment, which mediates on the turnover intention of the employee. The level of transformational leadership, organizational culture and commitment on turnover intention is examined. The study conducted the confirmatory factor analysis and the model fit analysis via AMOS. The respondents were employees of the Malaysia Retail Chain Association members. Six companies were involved in the study with 389 respondents. The study utilized the simple random sampling technique, in the survey. The findings revealed that all the variables were tested with acceptable normality that permitted the researcher to use AMOS as an analysis tool. The result revealed significant relationships among the variables; whilst organizational commitment was a possible mediator. The model fit analysis proved to be good, displaying significant p-value, entailed with a strong pattern matrix for the constructs’ dimensions. The theoretical contribution of the study is that it shows strong linkages and influences of the four constructs toward each other in one single model, and demonstrates the understanding of the extent of prediction variables on turnover intention. The practical contribution is that it reveals a possible solution involving transformational leaders, emphasizing organizational commitment and acclimatizing the organizational culture in the retail and services industry scenario in order to reduce employees’ turnover.